2018
DOI: 10.1074/mcp.ra117.000538
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase Receptor Type G (PTPRG) Controls Fibroblast Growth Factor Receptor (FGFR) 1 Activity and Influences Sensitivity to FGFR Kinase Inhibitors

Abstract: Recently, FGFR1 was found to be overexpressed in osteosarcoma and represents an important target for precision medicine. However, because targeted cancer therapy based on FGFR inhibitors has so far been less efficient than expected, a detailed understanding of the target is important. We have here applied proximity-dependent biotin labeling combined with label-free quantitative mass spectrometry to identify determinants of FGFR1 activity in an osteosarcoma cell line. Many known FGFR interactors were identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…Although the mechanism of FGFR1 activation and signaling is well studied, the knowledge about trafficking of FGFR1 is far from complete. Recent proteomic studies revealed several proteins that may modulate intracellular transport of FGFR1, however, the exact role of these factors in FGFR1 trafficking awaits further studies [31,42]. FGFR1 is subjected to the constitutive low‐rate internalization from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of FGFR1 activation and signaling is well studied, the knowledge about trafficking of FGFR1 is far from complete. Recent proteomic studies revealed several proteins that may modulate intracellular transport of FGFR1, however, the exact role of these factors in FGFR1 trafficking awaits further studies [31,42]. FGFR1 is subjected to the constitutive low‐rate internalization from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently uncoupled FGFR1 dimerization from the receptor activation and have demonstrated that dimerization of FGFR1, but not receptor autophosphorylation, triggers CME of FGFR1 [5,6]. A number of proteins involved in CME of FGFR1 in response to FGF binding were identified,however, the exact role of a number of these factors in the receptor internalization is still largely mysterious [31,40–44]. Besides CME, clathrin‐independent endocytosis (CIE) may participate in FGFR1 internalization [34,45,46].…”
Section: Introductionmentioning
confidence: 99%
“…A homogenous clone with moderate FGFR4-GFP expression was chosen for further studies. U2OS cells stably expressing FGFR1-GFP and FGFR1-BirA-HA have been described (76). For generation of truncated SHIP2 variants, the C-terminal (17,45,81).…”
Section: Methodsmentioning
confidence: 99%
“…The cellular trafficking and function of FGFR1 depends on the receptor interaction with specific partner proteins. Up to date a few attempts to identify proteins that bind FGFR1 were reported [42,43]. Here, we sought to identify novel proteins that adjust FGFR1 function and cellular distribution.…”
Section: Fgfr1 Interactome Reveals Galectin Family Members As Novel Fmentioning
confidence: 99%
“…We used model U2OS-SBP-R1 cells producing streptavidin-binding peptide (SBP)-tagged FGFR1 (SBP-FGFR1) and U2OS-R1 cells stably expressing non-tagged FGFR1 as a control [43]. At steady state conditions FGFR1 is localized to the plasma membrane [44][45][46].…”
Section: Fgfr1 Interactome Reveals Galectin Family Members As Novel Fmentioning
confidence: 99%